Intraventricular rupture of brain abscess: report of two cases and review of the literature - Ramírez Quiñones, Jorge Alonso (2014)
Brain abscess is an infrequent infectious disease that has a good prognosis in most of the cases with timely diagnosis and suitable treatment. Intraventricular rupture is a rare complication of the brain abscess with high mortality. It is characterized by a sudden consciousness compromise with signs of meningeal irritation and radiological findings compatible with purulent drainage into the ventricles. Treatment includes administration of intravenous and intrathecal antibiotics associated to prompt surgical intervention to drain the abscess and intraventricular content. Two cases of brain abscess complicated with intraventricular rupture showing clinical and radiological features typical of this condition and favorable outcome with intravenous antibiotic treatment during six and ten weeks respectively are reported.